Reticulate acropigmentation of Kitamura with café-au-lait macules: a rare case report - Gao, Bukuan; Wang, Huijuan; Fan, Qianqian; Cong, Lin; Zhang, Guoqiang; Liu, Xiaoye (Frontiers in Medicine, 2025)
Reticulate acropigmentation of Kitamura (RAK) predominantly affects East Asian populations, though isolated cases and familial occurrences have been reported globally. Japanese researchers Kitamura et al. first described this condition in 1943. In 2013, pathogenic variants in ADAM10 (a disintegrin and metalloprotease 10) were identified as causative in multiple Japanese RAK pedigrees. The occurrence of RAK with Dowling-Degos disease (DDD) is relatively well-documented. However, rare associations with bilateral clinodactyly, nevus of Ito, dermatopathia pigmentosa reticularis, and progressive seborrheic keratosis have also been reported. RAK is an extremely rare autosomal dominant disorder. Café-au-lait macules (CALMs) represent common hyperpigmented lesions, yet no documented cases of RAK-CALMs coexistence exist in the literature to date.